2021
DOI: 10.5588/pha.20.0061
|View full text |Cite
|
Sign up to set email alerts
|

Trends in extrapulmonary TB cases at three teaching hospitals in Ghana, 2008–2017

Abstract: SETTING: Three teaching hospitals in Ghana.OBJECTIVE: To elucidate trends in demographics, clinical characteristics and treatment outcomes in extrapulmonary TB (EPTB) patients.DESIGN: This was a retrospective study involving the review and comparison of EPTB and pulmonary TB (PTB) data from 1 January 2008 to 31 December 2017 in TB registers and treatment cards.RESULTS: Of 15,392 TB cases, 4607 (30%) were EPTB, including 4477/4607 (97%) new cases. There were 2,679/4607 (58%) males and the age range was 0.3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The current study also found a high prevalence of EPTB, with almost half (48%) of the TB population diagnosed with EPTB. This was higher than reported rates of 29% and 20-30%, respectively, in previous local studies [21,22]. A similar study in a referral hospital in Ethiopia reported an EPTB proportion of 49.8% [27].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The current study also found a high prevalence of EPTB, with almost half (48%) of the TB population diagnosed with EPTB. This was higher than reported rates of 29% and 20-30%, respectively, in previous local studies [21,22]. A similar study in a referral hospital in Ethiopia reported an EPTB proportion of 49.8% [27].…”
Section: Discussioncontrasting
confidence: 60%
“…The cohort of TB patients reviewed was largely male, which has been observed in several studies involving TB patients [21][22][23]. The male-to-female ratio was estimated to be 1.6 : 1 by WHO although variable across countries [24].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing active TB disease is 20 to 37 times greater in HIV-infected persons than in HIV-uninfected persons [7]. In most high-burden TB/HIV countries, including Ghana, many of the estimated new TB cases are un-notifiable [8]. Only 64% of the estimated 10 million new TB cases in HIV-uninfected persons and A share 51% of the estimated 0.9 million new TB cases in HIVinfected persons were reported in 2017 [2].…”
Section: Introductionmentioning
confidence: 99%